2015
DOI: 10.1074/jbc.m115.676056
|View full text |Cite
|
Sign up to set email alerts
|

Lecithin:Cholesterol Acyltransferase (LCAT) Deficiency Promotes Differentiation of Satellite Cells to Brown Adipocytes in a Cholesterol-dependent Manner

Abstract: Significance: We present a novel lipid-based mechanism to recruit functional BAT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…Meanwhile, LCAT promoted the PPARγ signalling pathway at the protein and RNA levels, and the effects of LCAT overexpression and interference on preadipocyte differentiation were determined by qPCR and Oil red O staining. However, the research by Nesan et al showed that LCAT deficiency could promote the differentiation of cholesterol-dependent satellite cells into brown adipocytes [ 24 ]. This is contrary to our results, and the reasons for this difference are unclear.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Meanwhile, LCAT promoted the PPARγ signalling pathway at the protein and RNA levels, and the effects of LCAT overexpression and interference on preadipocyte differentiation were determined by qPCR and Oil red O staining. However, the research by Nesan et al showed that LCAT deficiency could promote the differentiation of cholesterol-dependent satellite cells into brown adipocytes [ 24 ]. This is contrary to our results, and the reasons for this difference are unclear.…”
Section: Discussionmentioning
confidence: 99%
“…This study is the first to clarify the role of LCAT m 6 A methylation during adipogenesis. Lecithin cholesterol acyltransferase (LCAT) is a key protein in the peripheral high-density lipoprotein metabolism pathway, which has been reported to be mainly involved in cholesterol reverse transport and energy metabolism [22][23][24]. To date, LCAT plays an important role in atherosclerosis and is associated with abdominal subcutaneous fat and abdominal visceral fat [25][26][27][28].…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, cholesterol from endogenous synthesis and dietary sources both contribute to hepatic inflammasome activation (27), in part through cholesterol crystal formation. The findings also uncovered a critical role for cellular cholesterol in modulating the spontaneous development of classical brown adipose tissue in skeletal muscle from myoblasts in utero and satellite cells in adults (28).…”
Section: Non-classical Metabolic Phenotypes Of Fld: Lessons From Murimentioning
confidence: 90%
“…In addition to the above‐mentioned proteins and transcriptional factors, lecithin cholesterol acyltransferase (LCAT) deletion can convert SCs to brown adipocytes (Nesan et al, 2015). Ectopic expression of nuclear factor I‐A (NFIA) in myoblasts induces them to brown adipocyte differentiation (Hiraike et al, 2017).…”
Section: Factors Inducing Myoblast To Adipocyte Differentiationmentioning
confidence: 99%